1990
DOI: 10.1016/0304-3959(90)91157-e
|View full text |Cite
|
Sign up to set email alerts
|

The selective serotonin reuptake inhibitor paroxetine is effective in the treatment of diabetic neuropathy symptoms

Abstract: The effect of the selective serotonin reuptake inhibitor paroxetine on diabetic neuropathy symptoms was examined in comparison to imipramine and placebo in a randomised, double-blind, cross-over study. Paroxetine was given as a fixed dose of 40 mg/day, while the dose of imipramine was adjusted to yield optimal plasma levels of imipramine plus desipramine of 400-600 nM. Paroxetine significantly reduced the symptoms of neuropathy as measured by both observer- and self-rating, but was somewhat less effective than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
193
2
7

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(205 citation statements)
references
References 26 publications
3
193
2
7
Order By: Relevance
“…This benefit occurred within the first week (Fig. 2), as has been found in another antidepressant pain study [4], but not in all [3,101. The benefit was shown compared with both placebo and baseline.…”
Section: Discussionsupporting
confidence: 65%
“…This benefit occurred within the first week (Fig. 2), as has been found in another antidepressant pain study [4], but not in all [3,101. The benefit was shown compared with both placebo and baseline.…”
Section: Discussionsupporting
confidence: 65%
“…14 In the treatment of painful diabetic neuropathy, Sindrup et al found improvement in patients treated with paroxetine who either were not depressed or did not experience an antidepressant effect as measured by the Beck Depression Inventory. 17,18 In contrast, Max et al found that fluoxetine was more effective than placebo only in the subgroup of depressed patients. 16 In fibromyalgia, Goldenberg et al found improvement in the fluoxetine group despite no change in their Beck Depression Inventories.…”
Section: Discussionmentioning
confidence: 96%
“…Sindrup et al found that imipramine relieved diabetic neuropathy more effectively than paroxetine. 17 Max and colleagues found a significant improvement in diabetic neuropathy with amitriptyline and desipramine, but not with fluoxetine. 16 Bendtsen et al found improvement in tension-type headache with amitriptyline, but not citalopram.…”
Section: Discussionmentioning
confidence: 99%
“…2,26 In fact, only a few SSRIs proved effective for neuropathic pain in clinical trials. 45,46 After nerve injury, the 5-HT content in the lesioned nerve increases. 5-HT receptors of the 5-HT3 and 5-HT2A subtype are present on C-fibers.…”
Section: Discussionmentioning
confidence: 99%